A Avaliação departamental: Dificuldades e Perspectivas - Barreto, José Anchieta Esmeraldo; Barreto, Ana Maria Esmeraldo; Marques, Soraia de Figueiredo; Viana, Ùrsula Maria Pereira; Magalhâes, Suzana Marly da Costa (Estudos em Avaliação Educacional, 1991)